1998
DOI: 10.1152/ajpgi.1998.274.6.g1068
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelin synthesis in hepatic endothelial cells

Abstract: Endothelin (ET) stimulates vasoconstriction and glucose production and mediator synthesis in the liver. Only hepatic endothelial cells express ET-1 mRNA, and during endotoxemia in the intact rat, a ninefold increase in hepatic ET-1 mRNA occurs within 3 h of lipopolysaccharide (LPS) infusion [A. T. Eakes, K. M. Howard, J. E. Miller, and M. S. Olson. Am. J. Physiol. 272 ( Gastrointest. Liver Physiol. 35): G605–G611, 1997]. The present study defines the mechanism by which hepatic ET production is enhanced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Previous studies have indicated that microvascular perfusion failure significantly contributes to the manifestation of endotoxic liver injury [38], as again underlined by the significant negative correlation between hepatocellular excretory function and perfusion failure. The mechanisms, which are involved in the development of sinusoidal perfusion failure in endotoxemia are thought to be based on the action of TNF-a, including intravascular congestion [39], endothelial cell swelling [40], and release of endothelin-1 [41,42]. Thus, the protection from perfusion failure by CpG-ODN observed in our experiments may also be due to the downregulation of the proinflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have indicated that microvascular perfusion failure significantly contributes to the manifestation of endotoxic liver injury [38], as again underlined by the significant negative correlation between hepatocellular excretory function and perfusion failure. The mechanisms, which are involved in the development of sinusoidal perfusion failure in endotoxemia are thought to be based on the action of TNF-a, including intravascular congestion [39], endothelial cell swelling [40], and release of endothelin-1 [41,42]. Thus, the protection from perfusion failure by CpG-ODN observed in our experiments may also be due to the downregulation of the proinflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, other cytokines and the extracellular matrix are prominent in many forms of wounding and are likely to be important regulators of ET-1 in this environment. Nonetheless, TGF-␤ has been reported to lead to increased production of ET-1 in other systems (Kurihara et al, 1989;Kanse et al, 1991;Schnermann et al, 1996Eakes andOlson, 1998), consistent with its effect in liver wounding. In these reports and in systems in which other factors stimulate ET-1 synthesis, the effect has been largely via modulation of precursor ET-1 (i.e., preproET-1 mRNA expression), primarily at the level of preproET-1 mRNA transcription.…”
Section: Et-1 Regulation In Wound Healingmentioning
confidence: 77%
“…KCs were cultured for 48 h at 37°C in a 10% CO 2 atmosphere prior to conducting all receptor characterization experiments. Kupffer cell and liver endothelial cell primary cultures are known to be highly enriched (95%) for the specified cell type as determined by peroxidase staining (KC marker) and acetylated low-density lipoprotein incorporation (LEC marker) (24). Hepatocytes were isolated as described by Seglen (25) and plated on Corning 24-well plates at 1 ϫ 10 5 cell/well in William's E Medium (Life Technologies, Inc.) supplemented with 10% fetal bovine serum (Hyclone) and 7 mg/liter insulin.…”
Section: Methodsmentioning
confidence: 99%